Effect of The Camposition Nanocomposite Fe3O4-Graphene Oxide on Optical Properties Synthesized from Coconut Shell Charcoal - Angraini, Sri; Gusnedi, Gusnedi; Jonuarti, Riri; Jhora, Fadhila Ulfa (Department of Physics, Universitas Negeri Padang, 2024)
This study aims to determine the effect of Fe3O4 nanocomposite composition: Graphene Oxide on the optical properties of Fe3O4 Graphene Oxide nanocomposite by obtaining the results of absorbance value, transmittance, reflectance, and band gap value based on UV-Vis test. Graphene oxide used in this study is made from biomass waste coconut shell charcoal which contains carbon elements, most of whose pores are still covered by hydrocarbons and other organic compounds and the charcoal is used as activated carbon through an activation process, then synthesized using the modified hummers method. In this study, three variations were used, namely 20%: 80%; 30%; 70%; 40%: The results show that the effect of Fe3O4-Graphene Oxide Nanocomposite Composition on coconut shell waste using a UV-Vis spectrometer, the absorbance value of each sample was obtained in the range of 200-290 nm.. In the results of gap energy research with 3 variations respectively 3.269 eV, 3.79 eV, 3.91 eV obtained that if the variation of graphene oxide is higher than the value of the energy gap produced is smaller, so the addition of graphene oxide from coconut shell waste has the effect of reducing the energy gap of graphene oxide.